Biomineralization: From Material Tactics to Biological Strategy. Issue 14 (23rd February 2017) - Yao, Shasha; Jin, Biao; Liu, Zhaoming; Shao, Changyu; Zhao, Ruibo; Wang, Xiaoyu; Tang, Ruikang
Abstract : Biomineralization is an important tactic by which biological organisms produce hierarchically structured minerals with marvellous functions. Biomineralization studies typically focus on the mediation function of organic matrices on inorganic minerals, which helps scientists to design and synthesize bioinspired functional materials. However, the presence of inorganic minerals may also alter the native behaviours of organic matrices and even biological organisms. This progress report discusses the latest achievements relating to biomineralization mechanisms, the manufacturing of biomimetic materials and relevant applications in biological and biomedical fields. In particular, biomineralized vaccines and algae with improved thermostability and photosynthesis, respectively, demonstrate that biomineralization is a strategy for organism evolution via the rational design of organism‐material complexes. The successful modification of biological systems using materials is based on the regulatory effect of inorganic materials on organic organisms, which is another aspect of biomineralization control. Unlike previous studies, this study integrates materials and biological science to achieve a more comprehensive view of the mechanisms and applications of biomineralization. Abstract : Biomineralization studies focus on the mediation function of organic matrices on inorganic minerals, which helps scientists to design and sythesize bioinspired functional materials. At the same time, the modification of biological systems using materials is based on the regulatory effect of inorganic materials on organic organisms, which is the aspect of biomineralization control.